The Effect of the Bioactive Glass and the Er:YAG Laser on the Remineralization of the Affected Dentin: A Comparative In Vitro Study - Moghaddas, Mohammad Javad; Moosavi, Horieh; Yaghoubirad, Sara; Chiniforush, Nasim (Journal of Lasers in Medical Sciences, 2020)
Introduction: The purpose of this study was to compare the effect of the bioactive glass, the glass ionomer, and the Erbium YAG laser as liners on the remineralization of the affected dentin. Methods: The present study was conducted on 64 healthy extracted human molars divided into 4 groups, 1 control group and 3 experimental groups. After artificially inducing dentinal caries lesions, each of the experimental groups was applied to the cavity floor and then restored with a composite. The samples were stored after thermocycling in an incubator for two months. Finally, the hardness of the cavity floor was measured at 3 depths of 20, 50 and 100 μm by the Vickers microhardness tester. The dentin conditions underneath the liners were also evaluated with FESEM. Statistical analysis was performed by two-way ANOVA and the post-hoc Games-Howell test (P < 0.05). Results: Among the groups, the lowest microhardness value was in the control group (P < 0.05) except at a depth of 100 μm; therefore, there was no significant difference between the control group and the bioactive glass (P > 0.05). The laser group had the highest microhardness value, which was significantly different from the control group (P < 0.05). There was a significant difference between the laser and bioactive glass (P < 0.05), except at a depth of 20 μm. The laser and glass ionomer had only a significant difference at a depth of 100 μm (P < 0.05). The microhardness value induced by glass ionomer was higher than bioactive glass, which in no depth was significant (P > 0.05). Partial dentinal tubule occlusion was observed with FESEM in each of the experimental groups as compared to the control group. Conclusion: The microhardness values were higher in all groups than in the control group. The laser might be more successful in remineralization than the other ones.